Violet Archer’s “The Twenty-Third Psalm” (1952): An Analytical Study of Text and Music Relations through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica J (Université d'Ottawa / University of Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer’s “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David’s faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
Keywords: Violet Archer; Canadian music; text and music relations; Fibonacci numbers; melodic contour; motivic analysis; Psalm 23; theory; music analysis; “The Twenty-Third Psalm” (1952); contemporary music; Robert D. Morris; Elizabeth West Marvin and Paul A. Laprade